The Relationships Between Female Adolescents' Media Use, Indoor Tanning Outcome Expectations, and Behavioral Intentions. (June 2017) - Myrick, Jessica Gall; Noar, Seth M.; Kelley, Dannielle; Zeitany, Alexandra E.
Background . Unlike other types of cancer, skin cancer incidence rates are on the rise and adolescent females are particularly likely to tan indoors, a major risk factor. However, little research has examined the role of media use in encouraging or discouraging this dangerous behavior in this population. Aims . To empirically assess the links between media use, indoor tanning-related outcome expectations, and behavioral intentions. Method . A survey of adolescent females ( N = 510) ages 15 to 18 in the Southeastern United States assessed demographics, types of media use, and indoor tanning intentions. Results . Significant correlations between media use and indoor tanning outcome expectations were found. Use of interpersonal and social media (i.e., talking on the phone, texting, and online social media) were positively associated with positive outcome expectations about indoor tanning and negatively associated with negative outcome expectations. A path analysis revealed that interpersonal/social media use had indirect associations with indoor tanning intentions via tanning outcome expectations. Mass media use (e.g., news media, entertainment media, and magazines) was not significantly associated with most indoor tanning outcome expectations but did have a direct negative association with behavioral intentions. Discussion . There are important relationships between media use, indoor tanning outcome expectations, and behavioral intentions. Interpersonal and social media use may help cultivate outcome expectations that encourage indoor tanning, which in turn may increase intentions to tan, while news media consumption in particular may reduce intentions to tan. Conclusion . These findings highlight the social nature of adolescent females and point to specific intervention channels for reducing indoor tanning among this population.